Clonagem, sequenciamento e caracterização parcial dos genes relacionados à lectina de Vatairea macrocarpa - Alves Filho, João Garcia (2008)
In this paper is made a description of three distinct genes that encode Vatairea macrocarpa lectin and related proteins. The sequences were obtained by amplification of genomic DNA and cDNA of leaves using semi - degenerate primers constructed from the information of the amino acid sequence of VML lectin deposited in GenBank. The result of sequencing rev eals the presence of three different genes, called contig 1, 2 and 3 . The VML lectin corresponds to contig1 long as one assumes that the lectin contains heterogeneities deposited VML or ambiguities arising in the Edman degradation . The translation of cont igs 2 and 3 show sequence identity of 77% compared to VML. Sequences, despite having conserved regions show differences in amino acid N - glycosylation sites, carbohydrate binding sites and metals and the presence of cysteine residues suggests that these pro teins may have other biological activities . The analysis of the sequence obtained by 3 'RACE proved complementary to contig3. Thus, the sequence contig3/contigA hybrid has two cysteine residues in addition to revealing differences in amino acid C - terminal region when aligned with other legume lectins. Phylogenetic analysis revealed that the observed contigs form a monophyletic group and has high similarity with lectins from Robinia pseudoacacia Sohora japonica and, in addition to the lectin - related protein Cladrastis lutea.